EVALUATION OF CHANGES IN SERUM GLUCOSE AND HbA1c LEVELS AFTER 3 MONTHS OF TREATMENT IN NEWLY DIAGNOSED TYPE 2 DIABETES PATIENTS AT THO XUAN GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate changes in serum glucose and HbA1c concentrations after 3 months of treatment in newly diagnosed type 2 diabetes mellitus (T2DM) patients at Tho Xuan General Hospital, Thanh Hoa, in 2025.Subjects and Methods: A cross-sectional analytical study combined with longitudinal follow-up was conducted on 137 patients diagnosed with T2DM for the first time at Tho Xuan General Hospital from January 2025 to June 2025.Results: The study on 137 newly diagnosed T2DM patients showed that after 3 months, metabolic indices improved with statistical significance (p
Keywords: Type 2 diabetes mellitus, HbA1c, serum glucose, Tho Xuan